Structural Investigation of Park’s Nucleotide on Bacterial Translocase MraY: Discovery of Unexpected MraY Inhibitors - Chen, Kuo-Ting (Sci Rep, 2016)
Systematic structural modifications of the muramic acid, peptide, and nucleotide moieties of Park’s nucleotide were performed to investigate the substrate specificity of B. subtilis MraY (MraY(BS)). It was found that the simplest analogue of Park’s nucleotide only bearing the first two amino acids, l-alanine-iso-d-glutamic acid, could function as a MraY(BS) substrate. Also, the acid group attached to the Cα of iso-d-glutamic acid was found to play an important role for substrate activity. Epimerization of the C4-hydroxyl group of muramic acid and modification at the 5-position of the uracil in Park’s nucleotide were both found to dramatically impair their substrate activity. Unexpectedly, structural modifications on the uracil moiety changed the parent molecule from a substrate to an inhibitor, blocking the MraY(BS) translocation. One unoptimized inhibitor was found to have a K(i) value of 4 ± 1 μM against MraY(BS), more potent than tunicamycins.